Penguatan Kognitif Dan Emosional Ibu Dengan Peran Ganda Dalam Mempertahankan Rumah Tangga - Sasmita, Windy; Hadi, Syamsul (Jurnal Bimbingan dan Konseling Islam, 2023)
This research was carried out using group counseling services provided by Civil Society Organizations (CSOs). The group counseling process aims to help mothers with multiple roles in maintaining their household and resolving the problems they face. This research uses a qualitative descriptive approach. The research subjects consisted of 3 mothers with dual roles aged 33-46 years and working as cadres in OMS. The data analysis used is data reduction, data presentation, and drawing conclusions. The results of the research show that cognitive and emotional strengthening efforts begin with the pre-counseling process, the initial stage, the work stage and the final stage. Mothers with multiple roles receive education and positive enthusiasm while participating in group counseling activities held at OMS. Apart from that, mothers with dual roles felt that while attending group counseling mothers with dual roles were able to solve problems because there were many solutions and motivation provided so that mothers with dual roles were able to think rationally in making decisions in an effort to maintain their household.